Consumer Expectations: A Residual Based Approach. (5th February 2016) - Rehman, Fahd; Cooper, Russel J.
Abstract : This paper presents an economy‐wide consumer expectations indicator that reflects different degrees of optimism or pessimism with respect to consumers' confidence in their economy. The indicator provides a useful complement to traditional economic indicators that are frequently used to compare countries, such as gross domestic product (GDP) in purchasing power parity (PPP) terms. Our indicator may be seen as representing the influence of social wealth on economic behavior–that is, of effects left out of a standard economic analysis. We use a theoretical approach to integrate the expectations measure with the International Comparison Program's (ICP) PPP GDP statistics which produces a measure we term "effective GDP." Compared to the ICP's PPP figures, the measure of "effective GDP" differs from the ICP's PPP estimates by as much as four to five percent in the positive direction for apparently optimistic countries and as much as two percent downwards for pessimists.